Biting the bullet: how to secure access to drylands resources for multiple users - Mwangi, Esther; Dohrn, Stephan (International Food Policy Research Institute, 2006)
Close to one billion people worldwide depend directly upon the drylands for their livelihoods. Because of their climatic conditions and political and economic marginalization drylands also have some of the highest incidents of poverty. Pastoral and sedentary production systems coexist in these areas and both very often use common property arrangements to manage access and use of natural resources. Despite their history of complementary interactions, pastoralists and sedentary farmers are increasingly faced with conflicting claims over land and other natural resources. Past policy interventions and existing regulatory frameworks have not been able to offer lasting solutions to the problems related to land tenure and resource access; problems between the multiple and differentiated drylands resource users, as part of broader concerns over resource degradation and the political and economic marginalization of the drylands. This paper discusses enduring tension in efforts to secure rights in drylands. On the one hand are researchers and practitioners who advocate for statutory law as the most effective guarantor of rights, especially of group rights. On the other side are those who underscore the complexity of customary rights and the need to account for dynamism and flexibility in drylands environments in particular. It explores innovative examples of dealing with secure access to resources and comes to the conclusion that process, rather than content, should be the focus of policy makers. Any attempt to secure access for multiple users in variable drylands environments should identify frameworks for conflict resolution, in a negotiated manner, crafting rules from the ground upwards, in addition to a more generalized or generic identification of rights. Elite capture and exclusion of women and young people continue to pose significant challenges in such decentralized processes. For rights to be meaningfully secured there is need to identify the nature and sources of threats that create insecurities